Leveraging the sport participation legacy of the London 2012 Olympics: senior managers' perceptions. Issue 2 (3rd April 2017) - Hayday, Emily Jane; Pappous, Athanasios (Sakis); Koutrou, Niki
ABSTRACT: The purpose of this study was to understand how a sports mega event (SME) was leveraged to try and increase participation, through the investigation of national governing bodies (NGBs) opinions and attitudes. Critical Realism (CR) was used as a tool to aid understanding of leveraging and legacy conceptualisation, through an empirical investigation. An extensive, mixed method online survey was conducted post London 2012 with senior staff members of NGBs, the main delivery agent chosen to support the participation initiatives associated with the London 2012 Olympics. This research provides valuable findings surrounding the use of CR as a tool to investigate legacy creation, whilst at the same time offering insights to enhance the policy implementation process within the sports development sector. The importance of communication, competitive nature of sports system, media, club engagement, organisational capacity and monitoring and evaluation were highlighted, which provided useful insights into the multidimensional constructs that can aid future leveraging strategies prior to hosting SMEs.